First season quiet observations: Measurements of cosmic microwave background polarization power spectra at 43 GHz in the multipole range 25 ≤ ℓ ≤ 475 - Bischoff, C; Brizius, A; Buder, I; Chinone, Y; Cleary, K; Dumoulin, R; Kusaka, A; Monsalve, R; Næss, S; Newburgh, L; Reeves, R; Smith, K; et al. (Institute of Physics Publishing, 2011)
The Q/U Imaging ExperimenT (QUIET) employs coherent receivers at 43GHz and 94GHz, operating on the Chajnantor plateau in the Atacama Desert in Chile, to measure the anisotropy in the polarization of the cosmic microwave background (CMB). QUIET primarily targets the B modes from primordial gravitational waves. The combination of these frequencies gives sensitivity to foreground contributions from diffuse Galactic synchrotron radiation. Between 2008 October and 2010 December, over 10,000hr of data were collected, first with the 19 element 43 GHz array (3458hr) and then with the 90 element 94 GHz array. Each array observes the same four fields, selected for low foregrounds, together covering ≈1000 deg2. This paper reports initial results from the 43 GHz receiver, which has an array sensitivity to CMB fluctuations of 69μK√s. The data were extensively studied with a large suite of null tests before the power spectra, determined with two independent pipelines, were examined. Analysis choices, including data selection, were modified until the null tests passed. Cross-correlating maps with different telescope pointings is used to eliminate a bias. This paper reports the EE, BB, and EB power spectra in the multipole range ℓ = 25-475. With the exception of the lowest multipole bin for one of the fields, where a polarized foreground, consistent with Galactic synchrotron radiation, is detected with 3σ significance, the E-mode spectrum is consistent with the ΛCDM model, confirming the only previous detection of the first acoustic peak. The B-mode spectrum is consistent with zero, leading to a measurement of the tensor-to-scalar ratio of r = 0.35+1.06-0.87. The combination of a new time-stream "double-demodulation" technique, side-fed Dragonian optics, natural sky rotation, and frequent boresight rotation leads to the lowest level of systematic contamination in the B-mode power so far reported, below the level of r = 0.1. © 2011. The American Astronomical Society. All rights reserved.